(untitled) (Progressive Agriculture, 2017)
The study was conducted to measure the contribution of women to their household income, to analyze the pattern of womens participation in decision making process, their perceptions and impact of income on decision making process. The study was carried out at three villages of Mymensingh Sadar Upazila. Data were collected from 50 rural households by random sampling technique with a structured questionnaire. The obtained data were analyzed by using tabular and different statistical techniques. The results of the study showed that the pattern of womens contribution to household income has been changed. In the study area, women were participating in various income generating activities such as crop production, post-harvest activities, poultry rearing, management of livestock and fisheries, etc. Male and female rendered their involvement in income generating activities for 220 man-days and 204 man-days per year, respectively. The average annual womens contribution to household income was estimated at Tk. 42000 per year which was about 43.52 percent of the total household income. The multiple regression analysis showed that womens income was positively related with womens education and farm size but negatively related with age, family size and indebtedness. A logistic regression analysis showed that womens participation in decision making process was negatively related with family size, but positively related with respondents age, education, farm size, income and occupation. Women rendered a great deal of contribution in making decision on post-harvest operation, management of production activities, selling of crops, rearing poultry, goat and cattle, purchasing of agricultural inputs, etc. To reduce their economic, social and political constraints, the study suggested providing logistic supports such as health care facility, credit facility, input supply, agricultural extension services, need-based training, etc. in order to increase their participation in income generating activities and different household decision making events. Progressive Agriculture 28 (2): 120-129, 2017